A CHO cell line engineered to express XBP1 and ERO1‐Lα has increased levels of transient protein expression. (20th March 2013) - Cain, Katharine; Peters, Shirley; Hailu, Hanna; Sweeney, Bernie; Stephens, Paul; Heads, James; Sarkar, Kaushik; Ventom, Andy; Page, Catherine; Dickson, Alan
<x xml:space="preserve">Abstract</x> Transient gene expression (TGE) systems currently provide rapid and scalable (up to 100 L) methods for generating multigram quantities of recombinant heterologous proteins. Product titers of up to 1 g/L have been demonstrated in HEK293 cells 1 but reported yields from Chinese hamster ovary (CHO) cells are lower at ∼300 mg/L.2 We report on the establishment of an engineered CHOS cell line, which has been developed for TGE. This cell line has been engineered to express both X‐box binding protein (XBP‐1S) and endoplasmic reticulum oxidoreductase (ERO1‐Lα) and has been named CHOS‐XE. CHOS‐XE cells produced increased antibody (MAb) yields (5.3– 6.2 fold) in comparison to CHOS cells. Product quality was unchanged as assessed by size, charge, propensity to aggregate, major glycosylation species, and thermal stability. To further develop and test this TGE system, five commercial media were assessed, and one was shown to offer the greatest increase in antibody yields. With the addition of a commercial feed, MAb titers reached 875 mg/L. © 2013 American Institute of Chemical Engineers Biotechnol. Prog., 29:697–706, 2013